The Effect of Playing Bridge Beams on the Coordination and Balance of the Body of Early Childhood - Amelia, Hafidzah; Hendratno, Hendratno; Jannah, Miftakhul (Universitas Malikussaleh, 2019)
This study aims to determine the effect of playing bridge beams on the coordination and balance of the body of children aged 5 - 6 years. The research subjects were children aged 5 - 6 years in Raudhatul Athfal (Kindergarten School) Munawwarus Sholeh of Situbondo district. The research approach used is a quantitative approach with a quasi-experimental design. Research data was obtained through tests given to children and documentation taken at the time of the study. Data analysis techniques in this study using independent sample t-test. The results of the data analysis show the number sig. 0,000 > 0,050, it shows that the null hypothesis is rejected so that it can be concluded that there is the influence of playing the bridge beams on the coordination and balance of the body of children aged 5-6 years.